Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.jml.2020.104154
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis and lingering misinterpretation of linguistic dependencies in native and non-native sentence comprehension

Abstract: Research on temporarily ambiguous "garden path" sentences (e.g., After Mary dressed the baby laughed) has shown that initially assigned misinterpretations linger after reanalysis of the temporarily ambiguous phrase in both native (L1) and non-native (L2) readers. L2 speakers have particular difficulty with reanalysis, but the source of this L1/L2 difference is debated.Furthermore, how lingering misinterpretation may influence other aspects of language processing has not been systematically examined. We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 85 publications
1
16
1
Order By: Relevance
“…It is also possible however that previous studies have overestimated L1/L2 differences owing to small sample sizes. Although we acknowledge that the absence of L1/L2 differences in the present study may be attributable to the lack of statistical power, our sample size is larger than the previous L2 studies that have observed L1/L2 differences in filler-gap dependency formation (e.g., Fujita & Cunnings, 2020; Marinis et al, 2005) and interference in reflexive resolution (Felser et al, 2009; Felser & Cunnings, 2012). Given that a small sample size potentially leads to overestimates of effect sizes (Vasishth et al, 2018), future research will need to test the replicability of the present study and previous ones.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…It is also possible however that previous studies have overestimated L1/L2 differences owing to small sample sizes. Although we acknowledge that the absence of L1/L2 differences in the present study may be attributable to the lack of statistical power, our sample size is larger than the previous L2 studies that have observed L1/L2 differences in filler-gap dependency formation (e.g., Fujita & Cunnings, 2020; Marinis et al, 2005) and interference in reflexive resolution (Felser et al, 2009; Felser & Cunnings, 2012). Given that a small sample size potentially leads to overestimates of effect sizes (Vasishth et al, 2018), future research will need to test the replicability of the present study and previous ones.…”
Section: Discussioncontrasting
confidence: 63%
“…There are several possible accounts of why the present study did not observe L1/L2 differences while some previous studies did. One is that L1/L2 differences in filler-gap dependencies arise only in certain circumstances, such as in sentences with filler-gap dependencies spanning several clauses or with increased processing cost due to revision (Fujita & Cunnings, 2020; Marinis et al, 2005). Another is that L2 speakers are susceptible to discourse saliency as suggested by Felser and Cunnings (2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the failure may be driven by many factors that are external to the research question under investigation: differences in the population and/or language studied, the natural variability in the dependent variable, lab settings, equipment, and protocols can come together to lead to very different outcomes. Indeed, it is possible that when it comes to studying subtle and highly variable aspects of human (IR)REPRODUCIBILITY IN PSYCHOLOGY AND PSYCHOLINGUISTICS (IR)REPRODUCIBILITY IN PSYCHOLOGY AND PSYCHOLINGUISTICS (2020), Brandt et al (2020), Brewer et al (2021), Bristol and Rossano (2020), Brothers and Kuperberg (2021), Brysbaert (2019), Bürki et al (2020), Chan et al (2020), Chetail (2020), Collins et al (2020), Corps and Rabagliati (2020), Dıéez-Álamo et al (2020), Falandays et al (2020), Fellman et al (2020), Floccia et al (2020), Fox et al (2020), Fujita and Cunnings (2020), Gagné et al (2020), Garnham et al (2020), Günther, Nguyen, et al (2020), Günther, Petilli, et al (2020), Hesse and Benz (2020), Hollis (2020), Humphreys et al (2020), Hwang and Shin (2019), Isarida et al (2020), Jäger et al (2020), Johns et al (2020), Kaula and Henson (2020), Lauro et al (2020), Lelonkiewicz et al (2020), Li et al (2020), Liang et al (2021), McKinley and Benjamin (2020),…”
Section: Introductionmentioning
confidence: 99%